1984
DOI: 10.1152/ajpregu.1984.247.6.r968
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of plasma vasopressin after drinking in dehydrated humans

Abstract: To study the effects of nonosmotic and nonvolumetric factors that may influence secretion of vasopressin, serum Na+, K+, and osmolality (Osm), hemoglobin, hematocrit, plasma arginine vasopressin (AVP), aldosterone (PA), and renin activity (PRA) were measured in five men and three women (26-50 yr, 73 +/- 4 kg) before and after 24 h of mild dehydration (food but no fluid) and seven times during the 1st h after rehydration with 10 ml/kg of tap water (17.5 +/- 0.5 degrees C) consumed in 105 s (range 35-240 s). Deh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
67
1
1

Year Published

1985
1985
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(73 citation statements)
references
References 0 publications
4
67
1
1
Order By: Relevance
“…When dehydrated animals drink water, both responses are inhibited before systemic rehydration is evident. In dogs and human subjects, the early signal that inhibits thirst and VP secretion has been related to the volume of fluid consumed, apparently detected by oropharyngeal receptors that monitor the swallowing of liquids regardless of whether water, isotonic saline, or hypertonic saline solution is consumed (2,13,24,32). However, recent experiments indicate that early inhibition of VP secretion in rats is not mediated by oropharyngeal receptors (17,29) because plasma VP levels (pVP) were not affected either when dehydrated rats ingested isotonic saline or when water was consumed but drained from the stomach through an open gastric fistula (29).…”
mentioning
confidence: 99%
“…When dehydrated animals drink water, both responses are inhibited before systemic rehydration is evident. In dogs and human subjects, the early signal that inhibits thirst and VP secretion has been related to the volume of fluid consumed, apparently detected by oropharyngeal receptors that monitor the swallowing of liquids regardless of whether water, isotonic saline, or hypertonic saline solution is consumed (2,13,24,32). However, recent experiments indicate that early inhibition of VP secretion in rats is not mediated by oropharyngeal receptors (17,29) because plasma VP levels (pVP) were not affected either when dehydrated rats ingested isotonic saline or when water was consumed but drained from the stomach through an open gastric fistula (29).…”
mentioning
confidence: 99%
“…This was not significant for distilled water, 1.8% and 2.7% NaCl, but significant for 0.9% NaCl. In a similar work by Geelen, et al, (1984), the authors reported a decrease in thirst after drinking hypertonic saline. Obika and Mowoe (1977), and Rolls, et al, (1980) had reported an earlier observation of a fall in TP in normal euhydrate subjects when hypertonic and/or hypotonic fluid load was administered.…”
Section: Discussionmentioning
confidence: 79%
“…This effect preceded any change in plasma osmolality (Geelen, Keil, Kravik, Wade, Thrasher, Barnes, Pyka, Nesvig & Greenleaf, 1984;Thrasher, Nistal-Herrera, Keil & Ramsay, 1981). It has been suggested that this fall in plasma AVP is due to an oro-pharyngeal neuroendocrine reflex (Thrasher et al 1981).…”
Section: By M Chowdhury and Marianne Fillenz University Laboratory mentioning
confidence: 85%